Implementation Of Unit X Tina Orima Forest Management Forest Management (KPH) Unity Of Bombana District, South Sulawesi Province - Gusman Agusalim; Sitti Marwah; La Baco La Baco (Jurnal Perencanaan Wilayah, 2020)
Development of Forest Management Units (KPH) has been established as a strategic objective for better forest management and requires full support from all parties in implementing it. This study aims to analyze the characteristics of the region in realizing the effectiveness and efficiency of forest management in the FMU Tona Orima FMU management area and to analyze the more intensive, optimal and sustainable Implementation of FMU Development in the FMU TU Orima FMU management area. This research was conducted at KPH Unit X Tina Orima, Bombana Regency, Southeast Sulawesi Province. Data collection was done by purposive sampling. The population in this study were all regions, communities and KPH employees / staff. Thus, the sample size is determined based on consideration of the selection of respondents based on the position and mastery of the knowledge / ability of the respondents involved in the Implementation of the Unit X Tina Orima Forest Management Unit in Bombana, Southeast Sulawesi. Data were analyzed with qualitative descriptive analysis and spatial analysis. The results showed that the Implementation of FMU Development starts from the determination of the area, with inseparable how to consider the characteristics of the area because it is one of the important factors in the management of FMU development in implementing wiser forest use. Implementation of FMU Development provides a solution to face obstacles and challenges in FMU development, as well as the formation of strengthening cooperation between institutions and parties. Thus the FMU can be a key institution for realizing forest sustainability and community welfare within the FMU management unit Tina Orima, Bombana Regency, Southeast Sulawesi Province, towards FMU independence.Keywords    : Implementation ,KPH, ,Regional Characteristics